A inclusão de alunos surdos nas escolas públicas. - Santana, Ana Carolina Silva Gomes de (Universidade Federal do Tocantins, 2023)
The objective of this monograph is to demonstrate the need to use the Brazilian Sign Language (LIBRAS) in public schools as the first language for the formation of the deaf student in their learning, and whether they are able to educate these students in an inclusive manner in accordance with the rights guaranteed by the Federal Constitution. In order to understand the emergence of prejudices around the deaf community, we have previously presented a part of the history of the education of the deaf. The trajectory of education from the medieval periods to the contemporary, the struggles conquered before society, with a focus on education, and how the insertion of the deaf in schools to the present occurred. The choice of this topic occurred after reflecting on the importance of quality education for all. For the deaf this is only possible through the Libras. And the empowerment in Libras would be one of the most appropriated mean for inclusion inside the classroom. This work was carried out through a bibliographical, qualitative and reflexive research, in which it was analyzed in this material that in the present day, the area of education needs improvement in its public policies regarding in inclusive education, because they leave to be desired in its effectiveness.